Analysis of Risk Factors for Hypertension at Pustu Petuk Ketimpun Palangka Raya - Hendra Budi (Jurnal Teknik Informatika C.I.T Medicom, 2022)
Hypertension is an asymptomatic condition, where high blood pressure in the arteries causes an increased risk of cardiovascular-related diseases such as stroke, heart failure, heart attack, kidney damage. The prevalence of hypertension in Central Kalimantan Province in 2018 was 34.5% and in Palangka Raya City was 35.84%. The purpose of this study was to determine the factors associated with hypertension in Pustu Petuk Ketimpun Palangka Raya. This type of research uses a cross sectional design. The population is patients who seek treatment at Pustu Petuk Ketimpun Palangka Raya and the research sample is 218 patients. The sampling technique was chosen by simple random sampling. Data analysis using chi square statistical test. The results showed that age (p-value = 0.0003373), gender (p-value = 0.000002151), excessive sugar consumption (p-value = 0.0001199), excessive salt consumption (p-value = 0, 000001993), alcohol consumption (p-value = 0.01815) and smoking (p-value = 0.03175) are risk factors for hypertension in patients at Pustu Petuk Ketimpun Palangka Raya, Central Kalimantan.